Metode Telenursing Keluarga untuk Meningkatkan Perawatan Paliatif Pasien Kanker Stadium Lanjut di Masa Pandemi COVID-19 - Mariam Dasat; Uswatul Khasanah; Sigit Mulyono; Zadam Marita (Journal of Telenursing (JOTING), 2022)
This study aims to provide an overview of the telenursing method used by families undergoing palliative care programs for advanced cancer patients during the COVID-19 pandemic. The method used is a qualitative design with a phenomenological approach model. Data collection techniques were carried out through in-depth interviews with six participants and were taken based on the snowball sampling method. The results showed that when undergoing a palliative care program, the experience experienced by the family was worried about being infected with COVID-19 and there was patient non-compliance in undergoing the palliative care therapy program, such as doing excessive physical activity, taking drugs irregularly and consuming prohibited foods. In conclusion, it is necessary to increase the telenursing method's ability for families undergoing palliative care programs for advanced cancer patients during the COVID-19 pandemic, especially in improving the ability to communicate with patients and the use of information technology. Keywords: COVID-19, Cancer, Palliative Care, Telenursing